Implementasi PBL Terintegrasi STEM dengan Flipped Classroom untuk meningkatkan Kemampuan Berpikir Sistem Siswa SMA pada Topik Usaha dan Energi - Rahayu, Sri; Abdurrahman, Abdurrahman; Susana, Wayan (Universitas PGRI Semarang, 2022)
This study aims to determine the effect of implementing STEM integrated PBL with Flipped Classroom to improve high school students' system thinking skills. The samples in this study were students of class X MIPA 2 and X MIPA 3 SMA Al-Kautsar Bandar Lampung in the academic year 2021/2022. The research design used is One Group Pretest Posttest. The data collection instrument used was a multiple-choice test sheet. The results showed that learning the STEM approach with the flipped classroom strategy was able to improve students' system thinking skills, this can be seen from the average N-gain value in the experimental class of 0.65, which is greater than the control class with an average N-gain value of 0.55 with medium category. This shows that the system thinking ability of the experimental class is more improved than the control class. Also, supported by data from the results of the Independent simple T-test hypothesis test, the Sig value is obtained. (2-tailed) of 0.000 means that the implementation of STEM integrated PBL with flipped classroom can improve students' system thinking skills on the topic of effort and energy.Keywords: PBL, STEM, Flipped Classroom.